Efficacy and safety of saxagliptin in combination with metformin as initial therapy in Chinese patients with type 2 diabetes: Results from the START study, a multicentre, randomized, double‐blind, active‐controlled, phase 3 trial. Issue 3 (26th October 2017) - Dou, Jingtao; Ma, Jianhua; Liu, Jun; Wang, Changjiang; Johnsson, Eva; Yao, Hui; Zhao, June; Pan, Changyu
Abstract : Aim: To assess the efficacy and safety of saxagliptin plus metformin over 24 weeks in pharmacotherapy‐naïve Chinese patients with type 2 diabetes mellitus and inadequate glycaemic control (HbA1c, 8.0%‐12.0%). Research Design and Methods: In this multicentre, double‐blind, active‐controlled study (The START study: NCT02273050, clinicaltrials.gov ), patients were randomized (1:1:1) to saxagliptin 5 mg plus metformin, saxagliptin 5 mg plus placebo or metformin plus placebo. Saxagliptin was taken once daily; metformin was taken once/twice daily and was titrated from 500 mg to a maximum of 2000 mg/d over 8 weeks. The primary end point was change in HbA1c from baseline to Week 24. Results: Data from 630 patients (66.5% men; mean age, 50.1 years; mean body mass index, 26.6 kg/m 2 ; mean HbA1c, 9.4%; mean diabetes duration, 0.81 years) were analysed. Mean reduction in HbA1c was greater with saxagliptin plus metformin (−3.0%) than with saxagliptin plus placebo (−2.1%; P < .001) or metformin plus placebo (−2.8%; P = .034). Changes in mean fasting plasma glucose, 120‐minute postprandial glucose, and 180‐minute postprandial glucose area under the curve were greater, and more patients achieved a therapeutic glycaemic response, with saxagliptin plus metformin than with either monotherapy. Hypoglycaemic events were infrequent (<2%). Incidence of adverse events was similar among groups; upper respiratory tract infection and diarrhoea were most common. Conclusions: Saxagliptin 5 mg plus metformin significantly improved glycaemic control compared with either monotherapy in treatment‐naïve Chinese patients with type 2 diabetes, and was well tolerated.